THE EFFECT OF ABUSIVE SUPERVISION AND ETHICAL CLIMATE ON ORGANISATIONAL DEVIANCE (Third Sector Social Economic Review, 2021)
The aim of this study is to analyze the impact of abusive supervision and ethical climate on organizational deviation. For this purpose, a field study was conducted in Selçuklu District of Konya Province. The population of the study carried out in January 2021 is civil servants working in public banks in Selçuklu district, and the sample consists of 106 employees determined according to simple random method in 19 branches of 3 public banks. The questionnaire form used in the field research consists of 45 statements, 8 of which are questions about demographic information and 37 of them are scale expressions prepared according to the Likert scale. The 15-statement Abusive Supervision Scale is the scale used in Tepper's (2000) study, which was adapted into Turkish by Ülbeği, Özgen, and Özgen (2014). The 7-statement Ethical Climate Scale is the is the 7 statement version developed by Schwepker Jr. (2001) from the 10 statement questionnaire formed by Qualls and Puto (1989). The 15-statement Organizational Deviation Scale was developed and adapted to Turkish by Demir (2009), using the studies of Hollinger and Clark (1982) and Robinson and Bennett (1995). As a result of the ANOVA and t-test analyses applied to the data obtained, it was concluded that some demographic variables such as age, education and marital status were effective on the participants' perceptions of abusive management, ethical climate and organizational deviation. Another finding obtained through correlation and regression analyses in the study is the indicators that the effect of abusive management on organizational deviation is significant, and that the effect of ethical climate is not significant statistically.
Keywords: Abusive Supervision; Ethical Climate; Organizational Deviance; Regression